Leadership in Public Health: an Italian learning experience. (30th September 2020) - Giovanazzi, G; Barbara, A; Parente, P; Restivo, V; Selle, V; Siddu, A; Silenzi, A; Trucchi, C; Voglino, G; gualano, M R
Abstract: Background: The "Public Health Leadership" Working Group of Italian Society of Public Health (S.It.I.) organized a two-days Workshop in Verona in January 2020. Leadership is linked to capacity of inspiring people to craft and achieve vision and goals, to provide mentoring, coaching and recognition and to encouragement empowerment, allowing other leaders to emerge and high quality of care. As in others country, in Italy investing in new generations is fundamental and far-sighted to create Leadership culture in tomorrow's professionals. Objectives: The Workshop aim was to immerse Public Health residents into Health Leadership. Two types of practical/interactive experiences (Design thinking and Barometer strategy) and three speakers' interventions aroused curiosity, suggesting innovative ways to manage emerging local and global healthcare problems. Are residents interested in Leadership? Do they think Leadership could influence, motivate and enable to contribute to organization effectiveness? Results: 100 residents (Male 52, Female 48), from 72% of Public Health Schools (26), attended Workshop: 46 of 1st, 23 of 2nd, 18 of 3rd and 13 of residency program last year. Satisfaction questionnaire was completed by 58 residents (7 points Likert scale from 1 [dissatisfied/not useful] to 7 [satisfied/useful]). 5.91 pts result in interventions satisfaction, increasing from 1st (5.84) to last year (6.00); interventions topics deepening results in 5.38 pts, decreasing from 1st (5.52) to last year (5.00). Overall satisfaction on practical/interactive activities was 5.89 and 5.83 pts results in these methodologies usefulness. Conclusions: Health Leadership is a hot topic for residents; during residency program Leadership in not a main theme and residents want to improve non-technical skills to realise organization high quality of care. The practical/interactive activities were a winning choice to capture attention and cultivate mutual trust. This experience could be adapted in other countries. Key messages: Teaching Leadership in Public Health is a main topic that needs to be strengthened in Public Health agenda. Italian Public Health residents are very interested in Health Leadership improvement during their trainings.